Undergoing high-risk pregnancy between light and darkness - Oliveira, Virgínia Junqueira; Madeira, Anézia Moreira Faria; Penna, Cláudia Maria de Mattos (Rev Rene, 2011)
This study aims to understand the meaning of high-risk pregnancy to a pregnant woman. The study was conducted through qualitative research and phenomenological approach. The philosophy of Merleau-Ponty was used as a theoretical support. Sixteen pregnant women assisted by the high-risk prenatal program of the Policlinica Municipal de Divinopolis/MG took part in the study. From the interview guided by the question: “What does it mean to you to carry a high risk pregnancy?” the analytical categories: 1.experience lived in the body/perception of the body: the expression of feelings during the high-risk pregnancy;2. Expectations about the labor: between light and darkness. The results highlight the demand for a more humane approach on treating patients during the high-risk pregnancy, having integrality as the most important agent to guarantee the quality of the assistance on both levels: specialized (in hospital) and essential care.